Factors predicting oral health behaviors among students age 13-15 years in Shushtar city, Iran - Seyedeh Zahra Marashi; Alireza Hidarnia; Seyedeh Somayeh Kazemi; Fatemeh Zarei (BMC, 2023)
Abstract Background Tooth decay and other oral health (periodontal) diseases are highly prevalent worldwide and present a significant economic burden. Oral health is particularly important for adolescents, as the World Health Organization has identified tooth decay as one of the most pressing global health issues. This study aims to identify predictors of oral health behaviors among students aged 13-15 years in the city of Shushtar, Iran. Methods The present research is a cross-sectional study that was conducted during the summer of 2022 on 415 adolescents from the first secondary school in Shushtar. Two standard questionnaires were used to collect data, consisting of demographic information and questions related to measuring awareness, attitude, performance, and self-efficacy regarding oral health behaviors among adolescents. The collected data was analyzed using SPSS 22 statistical software through descriptive statistics, Pearson correlation, and regression analysis. Results The average scores for awareness, attitude, self-efficacy in brushing teeth, self-efficacy in flossing, self-efficacy in going to the dentist, and adolescents' performance on oral health behaviors are 5.72 ± 2.06, 36.40 ± 6.36, 25.40 ± 7.49, 14.15 ± 6.06, 15.80 ± 5.59, and 14.01 ± 4.02, respectively. Conclusion Based on the results of this study, it can be concluded that adolescents have low levels of awareness, performance, self-efficacy, and a positive attitude towards oral health. Considering the significance of adolescence as a stage for shaping oral health behaviors and their impact on adulthood, it is recommended to increase awareness among adolescents and improve their health behaviors by conducting educational classes in schools.